Cultural Contents in Two English Textbooks in Indonesia: Representations and Sources of Culture - Elshadelin, Gisela; Yumarnamto, Mateus (Widya Mandala Catholic University Surabaya, 2020)
This study explores the representations of the cultural contents in English textbooks used in Indonesian contexts. The textbooks as the sources of data are two textbooks for grade 12 that represent local and global textbook. The first one was Bahasa Inggris, a textbook published and endorsed by Indonesian government and the other one was Think, a global textbook published by Cambridge. This study aims at finding out how different cultural sources are represented in the two textbooks. The findings show that the two textbooks have different emphasis regarding the culture they present in texts and their accompanying visual illustrations. Bahasa Inggris puts the emphasis on global and local cultural sources. Other cultures that are not representative to the two main sources are very limited. On the other hand, Think provides a wide array of representations for global and other cultures but not local Indonesian culture. We end our discussion with a conceptual implication on cultural sources in English language teaching (ELT) materials.